2013
DOI: 10.1007/s00468-013-0878-9
|View full text |Cite
|
Sign up to set email alerts
|

Source water, phenology and growth of two tropical dry forest tree species growing on shallow karst soils

Abstract: Seasonally dry tropical forests are dominated by deciduous and evergreen tree species with a wide range of leaf phenology. We hypothesized that Piscidia piscipula is able to extend leaf senescence until later in the dry season due to deeper and more reliable water sources than Gymnopodium floribundum, which loses leaves earlier in the dry season. Physiological performance was assessed as timing of leaf production and loss, growth, leaf water potential, depth of water uptake determined by stable isotopes, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 44 publications
2
19
0
3
Order By: Relevance
“…Our study is among the few investigating rooting patterns in complex karstic soils, characterized by very shallow soil profiles, coupled to complex fissures and cave systems where roots can penetrate, and that are often filled with clay soils representing potentially important water sources for plants (Estrada-Medina et al 2013a). Contrasting species-specific patterns of rooting depth in karst-type substrates have been previously reported by Nie et al (2012) in Southwest China, Querejeta et al (2007) and Estrada-Medina et al (2013b) in Mexico, but not by Kukowski et al (2013) in Texas nor by Swaffer et al (2014) in South Australia, where all sampled species were found to rely only on precipitation to sustain transpiration, and not on groundwater available in the depth of the Karst features. The Classical Karst area where this study was carried out might represent an ideal location for further studies on plant-soil relationships because of the abundance of natural caves allowing relatively easy collection of soil and root samples at great depth (Johnson et al 2014).…”
Section: Discussionmentioning
confidence: 60%
“…Our study is among the few investigating rooting patterns in complex karstic soils, characterized by very shallow soil profiles, coupled to complex fissures and cave systems where roots can penetrate, and that are often filled with clay soils representing potentially important water sources for plants (Estrada-Medina et al 2013a). Contrasting species-specific patterns of rooting depth in karst-type substrates have been previously reported by Nie et al (2012) in Southwest China, Querejeta et al (2007) and Estrada-Medina et al (2013b) in Mexico, but not by Kukowski et al (2013) in Texas nor by Swaffer et al (2014) in South Australia, where all sampled species were found to rely only on precipitation to sustain transpiration, and not on groundwater available in the depth of the Karst features. The Classical Karst area where this study was carried out might represent an ideal location for further studies on plant-soil relationships because of the abundance of natural caves allowing relatively easy collection of soil and root samples at great depth (Johnson et al 2014).…”
Section: Discussionmentioning
confidence: 60%
“…A similar relationship between tree size and (in that study) depth of water use; with larger trees preferentially tapping into more shallow water sources was found by Meinzer et al (1999) [45] in Panama. A study by Estrada-Medina et al (2013) [46] analyzed source water use by Piscidia piscipula in Northern Yucatan and found that this species appeared to use primarily shallow water sources. In that study however, only "trees" were sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Forest tree species that typically occur in karst environments show a variety of adaptive characteristics [8,9]. For example, some studies have reported that plants growing in shallow soils in karst regions can extend their roots vertically into the bedrock layers [10,11]. However, other studies have reported that in shallow soils in karst habitats, the vertical root growth of many plant species is highly constrained, and that plant roots typically extend horizontally rather than vertically [12,13].…”
Section: Introductionmentioning
confidence: 99%